(untitled) (Acta Scientiarum. Agronomy, 2014)
Plant population and arrangement should be properly designed to maximize the seed yield of short-height genotypes of castor (Ricinus communis L.) in each cropping season. Experiments were performed in the in the fall-winter cropping season of 2008 and 2009 in Botucatu, State of São Paulo, Brazil, to evaluate the effects of row spacing (0.45, 0.60, 0.75, and 0.90 m) and plant population (25,000, 40,000, 55,000, and 70,000 plants ha-1) on agronomical traits, yield components, seed yield, and oil yield of the genotype FCA-PB. A high plant density caused a reduction in plant survival and increased the first raceme insertion height, particularly in the year with the higher rainfall. The basal stem diameter, number of racemes per plant, and seeds per raceme were reduced by increasing the plant density. However, the seed and oil yields were minimally influenced by plant population density and row spacing because the castor plant compensated for a low plant population with a high number of racemes and seeds. The maximum seed yield was achieved with an estimated 0.64 m of row spacing and 50,107 plants ha-1 (i.e., 3.2 plants m-1).